Gold Mineralization during Progressive Deformation at the Main Reef Complex, Sheba Gold Mine, Barberton Greenstone Belt, South Africa (70be661f-0ee2-40a0-abd8-94be7e748fa0) - M. J. Robertson; E. G. C Charlesworth (Canadian Institute of Mining, Metallurgy and Petroleum, 1994)
"Gold mineralization in the Main Reef Complex at Sheba Gold Mine is hosted within shear zones in a sequence of shales and greywackes of the Fig Tree Group. Competency contrasts between these rocks and a steeply dipping chert unit provided a locus for the development of right lateral steeply dipping shear zones. A set of flatter dipping shear fractures crosscut these zones with their intersections defining a system of en échelon ore shoots. Mineralization is both of vein type and disseminated strata-controlled replacement type. The latter occurs mainly within the wall rocks to the shear zones. Arsenopyrite and pyrite are the major sulfides, with arsenopyrite being confirmed largely to greywacke beds and pyrite to the more iron-rich shale units. Gold was introduced, together with minor sphalerite, pyrrhotite, chalcopyrite and early arsenopyrite, toward the end stages of a first pyrite phase. The mineralizing fluids were introduced along dilated cleavage planes and, emanating from these, produced a series of replacement fronts. Mineralization was syntectonic to late tectonic and occurred under conditions of progressive deformation, resulting in sulfides which are concentrated in the hinges of shear-related folds and semimassive sulfides within tension fractures which are folded, attenuated and fractured. An analysis of the structures shows a sequence of events in which an initial ductile simple-shear event with a steep sense of movement was succeeded by a more brittle strike-slip event. Mineralization is temporally related to the latter. This evolution in structural style was probably related to reactivation of the Sheba Fault as a transcurrent fault during emplacement of large granitoid bodies."